Socialism in Canada: A Study of the CCF-NDP in Federal and Provincial Politics - Thompson, John Herd (Labour / Le Travail, 1980)
This article reviews the book, "Socialism in Canada: A Study of the CCF-NDP in Federal and Provincial Politics," by Ivan Avakumovic.